Analisis Perhitungan Pajak Penghasilan Orang Pribadi Atas Wajib Pajak Penerima Upah Harian Dan Upah Borongan Sesuai Dengan Ketentuan Undang – Undang Harmonisasi Peraturan Perpajakan (Hpp): (Studi Kasus Pada Ud Memory Nganjuk) - Eni Srihastuti; Beby Hilda Agustin; Riko Cahyo Suntoro (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research is to determine the calculation of personal income tax for taxpayers receiving daily wages and piece wages in accordance with the law on harmonization of tax regulations. The data collected is quantitative data with data collection techniques using surveys, interviews and documentation. The analysis technique used is quantitative descriptive based on the PPh 21 tax law for freelancers. Based on the calculation results, it is known that all casual employees of UD Memory Nganjuk who meet the criteria for tax deductions according to PPh Article 21 are only daily employees in the foreman section. The foreman's daily employee earns more than Rp. 197,000.00 per day and in one month more than Rp. 1,970,000.00. For daily employees in the fields of glue, control, thread glue, shuttle testing, and quality selection, daily income of less than IDR 197,000.00 is not subject to tax. Meanwhile, UD Memory Nganjuk's contract employees receive zero tax deductions, because the daily income of contract employees is less than IDR 197,000.00 and their income in one month is less than IDR 1,970,000.00.